C0-C1f region of cardiac myosin binding protein-C induces pro-inflammatory responses in fibroblasts. (14th October 2021) - Lipps, C; Yogeswaran, A; McNamara, J; Wilhelm, J; Truschel, T; Aslam, M; Reischauer, S; Voss, S; Keller, T; Doerr, O; Nef, H; Hamm, C W; et al.
Abstract: Background: Cardiac myosin binding protein-C is a protein expressed in the myosin thick filament backbone that was recently described as a novel cardiac biomarker. Its N-terminal region, C0-C1f, is released within the first minutes of ischemia and plays a crucial role in the initiation of inflammation in bone marrow-derived macrophages. Long-term C0-C1f exposure induces cardiac fibrosis in transgenic mice; however, the mechanism by which C0-C1f causes fibrosis is unclear. The aim of the study was to investigate the effects of C0-C1f on fibroblasts, which are the main contributor to cardiac fibrosis, in vitro. We determined whether C0-C1f directly activates fibroblasts and causes a transdifferentiation to myofibroblasts or induces inflammatory responses. Moreover, we clarify whether other cell types could be involved in inducing fibrosis, i.e. by the release of pro-inflammatory cytokines upon C0-C1f interaction. Methods: A novel human fibroblast cell line (huFib) was treated with C0-C1f, C0-Linker, TGF-β, or LPS for different time periods. Inflammatory and fibrotic responses were evaluated at the RNA and protein level using different techniques including microarray, qRT-PCR, and immunofluorescence imaging. For signalling pathway analysis, TLR4 and NFκB were inhibited using chemical compounds TAK-242 or Bay11–0785 respectively. Results: C0-C1f treatment induced an increase in mRNA corresponding to pro-inflammatory genes in huFib cells (i.a. CXL1 upon 24 hours treatment: 29 fold, p<0.001 and CCL2 4-fold, p<0.001). The mRNA expression levels of pro-fibrotic genes such as ACTA2 or COL1A1, which were upregulated by TGF-β, were not reduced by C0-C1f (ACTA2 induced by TGF-β: 3, 8 fold, p<0.001, co-stimulation with C0-C1f: 1, 8 fold, p=0.11 compared to control; COL1A1 induced by TGF-β: 2, 94 fold, p<0.001, co-stimulation with C0-C1f: 2.09 fold (p<0.01) compared to control. Interestingly, co-stimulation of fibroblasts with C0-C1f and TGF-β led also to markedly lower inflammatory response compared to C0-C1f treatment alone (CXCL1 induction upon co-stimulation: 2, 0 fold, p<0.001, CCL2: 1, 9 fold, p=0.001, which is a reduction by 27 fold, p<0.001 or 2 fold, p=0.002, respectively). Inhibition of TLR4 or NFκB signaling diminished C0-C1f-mediated inflammatory responses. Conclusion: C0-C1f induces inflammation in fibroblasts via TLR4/NFκB signalling pathway. Downregulation of C0-C1f mediated inflammatory responses upon co-stimulation with TGF-β suggests crosstalk between the two signaling pathways. Contrary, C0-C1f reduced TGF-β mediated pro-fibrotic responses reflected by conversion of fibroblasts into myofibroblasts was not observed. Taken together, these data are consistent with the idea that C0-C1f might play a key role in the early initiation of inflammation upon myocardial infarction, also in fibroblasts, and that TGF-β acts as a counterpart at later stages of cardiac remodeling. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): William G. Kerckhoff Stiftung für wissenschaftliche Forschung und Fortbildung